ROBOTIC SANDING OF FREESTANDING BATHTUBS - Petrčić Antonio; Kralj Toni; Mihalić Tihomir; Šimunić Nikola (Journal of Energy Technology, 2025)
Modern production is characterized by great variability, with the possibility of making complex parts. However, as modern technology helps increase the efficiency of factors of production, it can also replace labour to reduce costs. For example, Artificial Intelligence and robotic systems are used in manufacturing, to achieve greater productivity and reduce costly human errors. That is why human resources are being replaced gradually by automated robotic systems. In this paper a novel approach was used to sand and polish freestanding bathtubs, using an industrial manipulator and a standardised procedure of sanding, with automatic detection of force when in contact with a part. This process resulted in over 30% of savings in consumable materials (sand paper, etc.) and an almost 50% increase in productivity. To conclude, using two robotic cells in the process of manufacturing of freestanding bathtubs produced four times greater labor saving in comparison to manual sanding.